History of the development of endocrinology in the Republic of Tatarstan - Farida Vadutovna Valeeva (Endocrinology Research Centre, 2014)
May 14, 2014 marks 200 years since the establishment of the Medical Department of the Imperial Kazan University (now Kazan State Medical University, KSMU). Since the XIX century, scientists of the Kazan Medical School studied physiology and pathology of the endocrine system. The first researchers were interested in the problems of endemic goitre, diabetes mellitus, and function of the adrenal glands. In 1976, the Endocrinology Department was organised in the Kazan State Medical Institute, the first among universities of the RSFSR. The head of the Department, V.V. Talantov, became the chief non-staff endocrinologist of the Ministry of Health of the Republic of Tatarstan (RT) and organiser of the Association of Endocrinologists in the RT. Moreover, he contributed to the organisation of the endocrine service in the republic and endocrinology began to be taught as an independent discipline. V.V. Talantov was a member of the Scientific Council of Endocrinology of the Russian Academy of Medical Sciences, Deputy Chairman of the Committee of Endocrinology Problems of the Ministry of Health, and a member of the editorial boards of four medical journals. The research in the field of endocrinology is now actively continued on the endocrinology course at KSMU. In-depth study of various aspects of the pathogenesis of diabetes and its complications was selected as the first-priority.